Localizing the Ã¢â‚¬Å“New SnapshotÃ¢â‚¬Â Textbook; A Study for Intermediate Level Students in Indonesia - Hartati, Rita (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
The purpose of this study is to analyze the Ã¢â‚¬Å“SnapshotÃ¢â‚¬Â textbook based on the local characteristics of Indonesian intermediate students. Therefore, the descriptive analysis method was applied to this study by using documentation and observation techniques. As a result, five elements need to be adapted based on the local characteristics of Indonesian students: 1) sociocultural content, 2) language level, 3) authenticity 4) instruction method, and 5) tests & exercises. Adapting the textbook-based local characteristics of students is not simple but it is important to achieve the learning objectives successfully.